Analysis of the need for the formation of competencies among future farmers for sustainable agriculture - Morozova Galina; Popova Irina; Berdyugin Artyom; Soroka Kirill; Sarycheva Varvara (E3S Web of Conferences)
The article considers the urgent problem of the quality of personnel provision in the agro-industrial complex of Russia, which affects both the results of agricultural production of individual industries and food supply of the population of the country, its security as a whole. In particular, the article: substantiates the need to develop such a quality as economic and legal competence in specialists in the field of agriculture; considers the reasons for the demand for the formation and development of professional competence and economic and legal competence in future agricultural producers; outlines the conceptual apparatus of the problem under study: clarifies the concepts of “need (demand) for a competent farmer”, “professional competence of a farmer” and “economic and legal competence of a farmer”; defines the structure of economic and legal competence of a farmer, including cognitive, motivational-value, operational and reflexive components; The conditions for its formation (classroom, extracurricular, electronic educational) and criteria (cognitive, activity-based, personal) are outlined.